Effect of ensiled crimped grape marc on energy intake, performance and gas emissions of beef cattle - Caetano, M.; Wilkes, M.J.; Pitchford, W.S.; Lee, S.J.; Hynd, P.I. (Animal feed science and technology, 2019)
•Lower digestibility of grape marc is a consequence of high lignin and tannin level.•Poor nutritional value of grape marc promotes high feed conversion of steers.•Grape marc has no impact on methane output per unit of gain or energy intake. The objective of the current study was to evaluate the effect of ensiled crimped grape marc (ECGM) on energy intake, growth performance, and emissions of carbon dioxide (CO2) and methane (CH4) in beef cattle. Twenty Angus steers (390 ± 38 kg initial BW; mean ± s.d.; 14 months of age) were used in a randomised design to test two diets: control (CON, roughage-based diet) and grape marc (GMD; 300 g/kg of ECGM containing 31.2 g/kg of condensed tannins in the total mixed ration on DM basis). Steers were randomly stratified by initial BW and then assigned to treatment and either an individual or group-housed pen. Steers were fed twice daily for a total of 41 d. Following diet adaptation, steers were moved between individual and group pens every 8 d for three rotations, allowing individual DM intake and faecal output measurements to be quantified. Carbon dioxide and CH4 emissions were measured using two, portable, automated, open-circuit gas quantification systems (GQS). There were no significant treatment differences in average daily gain (ADG), however the final BW was 5% greater for steers fed CON than those fed GMD (P < 0.01). Steers fed GMD consumed 4% more than CON-fed steers (P < 0.01), and thus the feed conversion ratio, measured as feed:gain, was 16% higher for the GMD group (P = 0.02). Dry matter digestibility (P < 0.01) and as a result, dietary metabolisable energy (ME) per kg of DM (P < 0.01) and ME intake (P = 0.03) were lower in GMD-fed steers. No differences between treatments were found when CO2 and CH4 emissions were expressed in g per kg of DM intake or MJ of ME intake. In conclusion, diets containing 300 g/kg of ECGM (31.2 g/kg of condensed tannins on DM basis) reduced the energy availability and had no impact on CH4 output when expressed per unit gain or metabolisable energy intake in growing beef steers.